Practical dehydration - Greensmith, Maurice (Woodhead Pub., 1998)
Practical Dehydration has long been known as a standard work in its field. This book provides an invaluable guide to the practicalities and logistics of a changing industry and particularly strong in its coverage of international practice. In addition to the original chapters on packaging, storing and quality control this new edition includes modern analysis of expanding sectors and new technologies.
Previous edition: London : Food Trade, 1971.
Includes index.
Keywords: Food -- Drying.; Factory management.; elektronické knihy; electronic books